Impact of the STAT1 N-terminal domain for fibrosarcoma cell responses to ɣ-irradiation. (9th July 2020) - Michaelis, Martin; Göder, Anja; Ginter, Torsten; Kröhnert, Ulrike; Kosan, Christian; Krämer, Oliver H.
Abstract: Type I/II interferons (IFNα, β/IFNɣ) are cytokines that activate signal-transducer-and-activator-of-transcription-1 (STAT1). The STAT1 N-terminal domain (NTD) mediates dimerization and cooperative DNA-binding. The STAT1 DNA-binding domain (DBD) confers sequence-specific DNA-recognition. STAT1 has been connected to growth inhibition, replication stress and DNA-damage. We investigated how STAT1 and NTD/DBD mutants thereof affect fibrosarcoma cells. STAT1 and indicated mutants do not affect proliferation of resting and IFNα-treated cells as well as checkpoint kinase signaling, and phosphorylation of the tumor-suppressive transcription factor p53 ensuing ɣ-irradiation. Of the STAT1 reconstituted U3A cells those with STAT1 NTD mutants accumulate the highest levels of the replication stress/DNA-damage marker S139-phosphorylated histone H2AX (ɣH2AX). This is similarly seen with a STAT1 NTD/DBD double mutant, indicating transcription-independent effects. Furthermore, U3A cells with STAT1 NTD mutants are most susceptible to apoptotic DNA fragmentation and cleavage of the DNA repair protein PARP1. These data provide novel insights into the relevance of the STAT1 NTD.